2009
DOI: 10.1080/01942630903008350
|View full text |Cite
|
Sign up to set email alerts
|

Household Task Participation of Children With and Without Attentional Problems

Abstract: Children with attention deficit/hyperactivity disorder (ADHD) often demonstrate problems in their participation in family occupations, such as household tasks, due to their needs for assistance and their behavior. Because participation in household tasks is part of family life and may be one way that families prepare children for adult roles, it is important to have a better understanding of the nature and extent of these difficulties. Forty-four parents of children in grades three through five (22 who had a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
1
22
0
6
Order By: Relevance
“…As previously reported by Dunn et al (2009), the groups did not differ significantly in the number of household tasks they performed, but children with ADHD required more assistance when performing household tasks.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…As previously reported by Dunn et al (2009), the groups did not differ significantly in the number of household tasks they performed, but children with ADHD required more assistance when performing household tasks.…”
Section: Resultssupporting
confidence: 70%
“…For parents of children with ADHD, efforts to organize and support their children's participation in household tasks, despite the stress they encounter, highlight the values that may underlie their efforts (Whalen et al, 2006). Indeed, parents of children with ADHD reported that their children performed similar numbers of household tasks as did parents of children without ADHD; however, parents of children with ADHD reported that their children required significantly more assistance when doing household tasks than did parents of children without ADHD (Dunn, Coster, Orsmond, & Cohn, 2009). …”
Section: Factors Influencing Children's Participation In Household Tasksmentioning
confidence: 90%
“…Except for the two maladaptive behavior domains, the proportion of children having normal level behaviors in the domains of work, self-care, home living, and functional academics was relatively low between 56% and 68%. These results suggest that children with ADHD exhibit common impairment behaviors in household tasks and educational functioning [25,26]. Surprisingly, for socialization and communication, the two common domains identified with deficit in ADHD children [9,13], the proportion of children exhibiting normal level adaptive function was relatively high (96% and 88%, in Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…ODD includes a pattern of negativistic, defiant, disobedient, and hostile behavior toward any authority figure 8,9 . Thus, it negatively affects the condition's course and prognosis, family dynamics, and the child or adolescent's academic and social functioning 10,11,12 . ODD increases the risk of conduct disorder and of antisocial personality disorder 13 and thus, it is essential to account for ODD symptoms in ADHD research.…”
Section: Introductionmentioning
confidence: 99%